Recent Advancement in Rational Design Modulation of MXene: A Voyage from Environmental Remediation to Energy Conversion and Storage. Issue 12 (14th September 2022) - Hayat, Asif; Sohail, Muhammad; Qadeer, A.; Taha, T. A.; Hussain, Majid; Ullah, Sami; Al‐Sehemi, Abdullah G.; Algarni, Hamed; Amin, Mohammed A.; Aqeel Sarwar, Muhammad; Nawawi, W. I.; Palamanit, Arkom; et al.
Abstract: Use of MXenes (Ti3 C2 Tx ), which belongs to the family of two‐dimensional transition metal nitrides and carbides by encompassing unique combination of metallic conductivity and hydrophilicity, is receiving tremendous attention, since its discovery as energy material in 2011. Owing to its precursor selective chemical etching, and unique intrinsic characteristics, the MXene surface properties are further classified into highly chemically active compound, which further produced different surface functional groups i. e., oxygen, fluorine or hydroxyl groups. However, the role of surface functional groups doesn't not only have a significant impact onto its electrochemical and hydrophilic characteristics (i. e., ion adsorption/diffusion), but also imparting a noteworthy effect onto its conductivity, work function, electronic structure and properties. Henceforth, such kind of inherent chemical nature, robust electrochemistry and high hydrophilicity ultimately increasing the MXene application as a most propitious material for overall environment‐remediation, electrocatalytic sensors, energy conversion and storage application. Moreover, it is well documented that the role of MXenes in all kinds of research fields is still on a progress stage for their further improvement, which is not sufficiently summarized in literature till now. The present review article is intended to critically discuss the different chemical aptitudes and the diversity of MXenes and its derivates (i. e., hybrid composites) in all aforesaid application with special emphasis onto the improvement of its surface characteristics for the multidimensional application. However, this review article is anticipated to endorse MXenes and its derivates hybrid configuration, which is discussed in detail for emerging environmental decontamination, electrochemical use, and pollutant detection via electrocatalytic sensors, photocatalysis, along with membrane distillation and the adsorption application. Finally, it is expected, that this review article will open up new window for the effective use of MXene in a broad range of environmental remediation, energy conversion and storage application as a novel, robust, multidimensional and more proficient materials. Abstract : The two‐dimensional MXenes were described and classified according to the synthesis techniques used, mechanical mixing, self‐assembly, in situ decorating, oxidation, properties and application. Herein, the MXenes and its derivates are emphasized onto the improvement of its surface characteristics for multidimensional application. This review article anticipating MXenes for emerging into environmental decontamination, photocatalysis, electrochemical use, and pollutant detection via electrocatalytic sensors, photocatalysis, along with membrane distillation and the adsorption application.